A national opinion study supports tobacco cessation by oral health professionals in Japan. (27th July 2017) - Nagao, Toru; Fukuta, Jinichi; Seto, Kanichi; Saigo, Keietsu; Hanioka, Takashi; Kurita, Kenichi; Tonai, Iwai; Yamashiro, Masashi; Kusama, Mikio; Satomura, Kazuto; Izumi, Yuichi; Mizutani, Koji; et al.
Background: Oral health professionals (OHPs) could have an important role in contributing to tobacco-dependence treatment of patients who visit dental clinics. How the public may perceive the role of OHPs in this capacity, however, has not been formally evaluated. The objective of this study was to assess national awareness and receptivity among Japanese in terms of the implementation of tobacco cessation counseling and treatment (TCCT) by OHPs in dental settings covered by National Health Insurance (NHI). The study participants' awareness and knowledge on tobacco-related health disparities were also examined. Method: A questionnaire survey was used to assess the opinions among patients who visited hospital dental and oral and maxillofacial departments and private dental clinics ( n = 27) spread across several prefectures in Japan on their acceptance if tobacco cessation services were given by dentists and dental hygienists. Result: Overall, 963 survey sheets were eligible for the analysis. To the inquiry on tobacco-related oral diseases (TRODs), majority were aware of tooth staining (85%) and bad breathe (80%). However, less than half of respondents were aware of oral cancer (47%) and only 32% of oral precancer. OHPs were acceptable to the majority of respondents for TCCT: ≥70 age-group (84%), ex-smokers (84%) or never smokers (81%), never drinkers (83%), and students (86%). Paradoxically, current smokers (60%) were less likely to accept OHP for TCCT. However, those willing to quit within a month (89%) were willing to accept any help from OHP than those with no decision to quit (58%) ( p = 0.029). Conclusion: The result of this nationwide survey in Japan supported an expansion of duties of OHPs to provide TCCT to dental patients covered by NHI. Japanese patients who were willing to quit smoking were likely to accept TCCT in a dental setting, supporting the scheme for the introduction of tobacco control in dentistry.